Li4SiO4 (at) rGO composite material for lithium ion battery as well as preparation method and application of Li4SiO4 (at) rGO composite material
By coating lithium tetrasilicon oxide (Li4SiO4) on reduced graphene oxide (rGO), the prepared Li4SiO4@rGO composite material is used as the positive electrode lithium supplement additive for lithium-ion batteries, solving the problems of capacity attenuation and performance of lithium-ion batteries, achieving high specific capacity and excellent cycling stability.
Patent Information
- Application Number
- CN202510246901.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium-ion batteries have problems of capacity attenuation and performance degradation in actual applications. The existing anode prelithiation technology has safety hazards and process complexity, and the performance of cathode prelithiated materials also needs to be improved.
Li4SiO4@rGO composite material is used as the positive electrode lithium supplement additive, and by coating lithium tetrasilicon oxide (Li4SiO4) on reduced graphene oxide (rGO), combining the advantages of Li4SiO4 and rGO, providing controllable electrochemical activity.
It achieves a high specific capacity of about 820 mAh/g, effectively replenishing the lithium ions lost during the battery operation, has excellent electrochemical performance and good cycle stability, is compatible with the existing battery manufacturing process, and is safe and reliable.
Smart Images

Figure CN119786614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy materials, and in particular to a Li4SiO4@rGO composite material for lithium-ion batteries, and a preparation method and application thereof. Background Art
[0002] As the core energy source for modern electronic devices, energy storage systems, and electric vehicles, the stability and durability of lithium-ion batteries are crucial to meeting the growing energy demand. However, in practical applications, the capacity decay and performance degradation of lithium-ion batteries have always troubled researchers. The reasons for capacity decay are varied, including but not limited to the safety hazards and process complexity of the pre-lithiation technology of anode materials, structural damage to cathode materials, decomposition of electrolytes, and micro-short circuits inside the battery.
[0003] Pre-lithiation technology is an effective way to solve the irreversible capacity loss during the first charge and discharge of lithium-ion batteries. Among them, anode pre-lithiation technology pre-deposits a layer of lithium on the surface of the anode to compensate for the lithium lost during the first charge and discharge process, thereby increasing the initial capacity of the battery. However, anode pre-lithiation technology has safety risks. For example, the use of lithium metal may cause battery short circuit and fire. In addition, the process complexity of anode pre-lithiation technology also limits its large-scale application.
[0004] Cathode pre-lithiation technology is another solution, which replenishes the lithium lost during the first charge and discharge process by introducing a lithium source into the cathode material. However, the performance of existing cathode pre-lithiation materials still needs to be improved. Although some materials have high specific capacity, they have problems such as poor cycle stability and incompatibility with existing battery manufacturing processes. Therefore, the development of a high-performance, easy-to-integrate and safe lithium supplement material is of great significance to promote the large-scale application of lithium-ion batteries. Summary of the invention
[0005] As the core energy source for modern electronic devices, energy storage systems, and electric vehicles, the stability and durability of lithium-ion batteries are crucial to meeting the growing energy demand. However, in practical applications, the capacity decay and performance degradation of lithium-ion batteries have always troubled researchers. The reasons for capacity decay are varied, including but not limited to the safety hazards and process complexity of the pre-lithiation technology of anode materials, structural damage to cathode materials, decomposition of electrolytes, and micro-short circuits inside the battery.
[0006] Pre-lithiation technology is an effective way to solve the irreversible capacity loss during the first charge and discharge of lithium-ion batteries. Among them, anode pre-lithiation technology pre-deposits a layer of lithium on the surface of the anode to compensate for the lithium lost during the first charge and discharge process, thereby increasing the initial capacity of the battery. However, anode pre-lithiation technology has safety risks. For example, the use of lithium metal may cause battery short circuit and fire. In addition, the process complexity of anode pre-lithiation technology also limits its large-scale application.
[0007] Cathode pre-lithiation technology is another solution, which replenishes the lithium lost during the first charge and discharge process by introducing a lithium source into the cathode material. However, the performance of existing cathode pre-lithiation materials still needs to be improved. Although some materials have high specific capacity, they have problems such as poor cycle stability and incompatibility with existing battery manufacturing processes. Therefore, the development of a high-performance, easy-to-integrate and safe lithium supplement material is of great significance to promote the large-scale application of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] The drawings described herein are used to provide further understanding of the present invention and constitute a part of this application. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0009] Figure 1 This is the SEM image of the Li4SiO4@rGO composite material (denoted as Li4SiO4@rGO) prepared in Example 1.
[0010] Figure 2 These are the SEM, TEM, and EDS images of the Li4SiO4@rGO composite material (denoted as Li4SiO4@rGO) prepared in Example 1, where the left image is the SEM and EDS images, and the right image is the TEM image.
[0011] Figure 3 This is the XRD pattern of the Li4SiO4@rGO composite material (denoted as Li4SiO4@rGO) prepared in Example 1.
[0012] Figure 4 This is the XPS graph of the Li4SiO4@rGO composite material (denoted as Li4SiO4@rGO) prepared in Example 1.
[0013] Figure 5 This is the SEM image of the material prepared in Comparative Example 1 (denoted as Li4SiO4).
[0014] Figure 6 This is the SEM image of the material prepared in Comparative Example 2.
[0015] Figure 7This is the charge and discharge curve of the Li4SiO4@rGO composite material prepared in Example 1 and the LFP positive electrode blended half-cell (0.2C, 1C=170mAh / g).
[0016] Figure 8 This is the cycling performance diagram of the Li4SiO4@rGO composite material prepared in Example 1 and the LFP positive electrode blended half-cell (0.5C, 1C=170mAh / g).
[0017] Fig. 9 This is the charge and discharge curve of the Li4SiO4@rGO composite material prepared in Example 1 and the NCM622 positive electrode blended half-cell (0.2C, 1C=174.5 mAh / g).
[0018] Fig.10 This is the cycling performance diagram of the Li4SiO4@rGO composite material prepared in Example 1 and the NCM622 positive electrode blended half-cell (1C, 1C=174.5 mAh / g). DETAILED DESCRIPTION
[0019] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0020] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0021] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0022] The preparation method of the Li4SiO4@rGO composite material of the present invention comprises the following steps: (1) Lithium nitrate (LiNO3) and silicon dioxide (SiO2) are mixed in a molar ratio of 3-5:1 and calcined at 650-800°C for 3-5h to obtain lithium orthosilicate powder, i.e., Li4SiO4 powder.
[0023] (2) Evenly dispersing Li4SiO4 powder in a solvent (the solvent is one or more of water, methanol, ethanol, and N-methylpyrrolidone), adding reduced graphene oxide (rGO), adding rGO to Li4SiO4 powder in a mass ratio of 1-30:99-70, and ball milling at a speed of 200-400 rad / min for 4-6 hours to obtain a Li4SiO4 / rGO solution.
[0024] (3) The Li4SiO4 / rGO solution is pumped into a spray dryer at a rate of 1-30 ml / min, and the inlet temperature is set to 130-180 °C to obtain Li4SiO4@rGO composite spheres, that is, Li4SiO4@rGO composite materials are obtained.
[0025] Example 1 A method for preparing a Li4SiO4@rGO composite material comprises the following steps: (1) Lithium nitrate (LiNO3) and silicon dioxide (SiO2) were mixed in a molar ratio of 4.2:1 and calcined at 700°C for 4 h to obtain lithium orthosilicate powder, i.e., Li4SiO4 powder.
[0026] (2) Li4SiO4 powder was evenly dispersed in deionized water, and reduced graphene oxide (rGO) was added in a mass ratio of rGO to Li4SiO4 powder of 15:85. The mixture was ball milled at a speed of 350 rad / min for 4 h to obtain a Li4SiO4 / rGO solution.
[0027] (3) The Li4SiO4 / rGO solution was pumped into the spray dryer at a rate of 10 ml / min, and the inlet temperature was set to 150 °C to obtain Li4SiO4@rGO composite spheres, that is, Li4SiO4@rGO composite materials.
[0028] Example 2 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (2), the addition ratio of reduced graphene oxide is adjusted to 5%wt, that is, the mass ratio of rGO to Li4SiO4 powder is 5:95.
[0029] Example 3 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (2), the addition ratio of reduced graphene oxide is adjusted to 25%wt, that is, the mass ratio of rGO to Li4SiO4 powder is 25:75.
[0030] Example 4 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (3), the inlet temperature is 130°C.
[0031] Example 5 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (3), the inlet temperature is 180°C.
[0032] Example 6 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (3), the pumping rate is 5 ml / min.
[0033] Example 7 This embodiment provides a method for preparing a Li4SiO4@rGO composite material, which is basically the same as that of Embodiment 1, except that in step (3), the pumping rate is 15 ml / min.
[0034] Comparative Example 1 This comparative example is basically the same as Example 1, except that rGO is not introduced and the sample is recorded as Li4SiO4. Figure 5 shown.
[0035] Comparative Example 2 This comparative example is basically the same as Example 1, except that the Li4SiO4 / rGO solution is not spray dried, but directly placed in an oven at 80°C for 12 hours. The SEM image is as follows: Figure 6 As shown, Li4SiO4 and rGO are obviously in a mechanically mixed state.
[0036] The SEM image of the Li4SiO4@rGO composite material prepared in Example 1 is as follows: Figure 1 As shown, it can be seen that the material has a high sphericity.
[0037] TEM and EDS images of the Li4SiO4@rGO composite material prepared in Example 1 are shown in Figure 2 As shown, it can be seen that Li4SiO4 is completely covered below the reduced graphene oxide layer.
[0038] The XRD image of the Li4SiO4@rGO composite material prepared in Example 1 is as follows: Figure 3 As shown, the peaks of the prepared Li4SiO4 correspond one to one with the standard card.
[0039] The XPS image of the Li4SiO4@rGO composite material prepared in Example 1 is as follows: Figure 4 shown.
[0040] The materials prepared in Examples 1-3 were subjected to electron microscopy test and conductivity test, and the measurement results are shown in Table 1. Table 1 Li4SiO4@rGO prepared at different rGO addition amounts.
[0041] Table 1 Relationship between rGO content and coating layer (reduced graphene oxide layer) thickness and conductivity
[0042] The data in Table 1 show that with the increase of rGO content, the coating thickness and conductivity both show an increasing trend. In particular, the conductivity increases significantly in magnitude when the rGO content increases. However, the growth of conductivity gradually slows down after the rGO content exceeds 15%, indicating that too much rGO may cause the conductive effect to tend to saturation. Therefore, considering the conductivity and coating thickness, 15% rGO content is the best, which makes the material have the best conductivity and stability.
[0043] The Li4SiO4@rGO composite materials prepared in Example 1, Example 4, Example 5, and Example 6 were mixed with the conductive agent Super P and the binder PVDF in a mass ratio of 7:2:1 to prepare an electrode slurry, which was coated on an aluminum foil substrate to prepare battery electrodes for electrochemical performance testing (measured at a current density of 100 mA / g). The results are shown in Table 2: Table 2 Electrochemical performance of each example
[0044] It can be seen from Table 2 that the inlet temperature and pumping speed of spray drying have a significant effect on the electrochemical properties of Li4SiO4@rGO. When the inlet temperature is too low, the sphericity is poor and the coating layer is too thick; when the inlet temperature is too high, the particle morphology will be distorted and the coating will be incomplete. When the pumping speed is too low, the mixing of Li4SiO4 and rGO is uneven, resulting in an unsatisfactory coating effect; when the pumping speed is too high, it may cause particle agglomeration, increase the particle size, and affect the uniformity of the material. Therefore, controlling the inlet temperature and pumping speed within a certain range can effectively improve the good electrochemical performance of Li4SiO4@rGO.
[0045] The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used as lithium supplement agents, and were mixed with LFP (lithium iron phosphate) and NCM622 at a ratio of 10%wt of the lithium supplement agent to form lithium ion half-cells.
[0046] Figure 7 Shown is the charge and discharge curve of Li4SiO4@rGO in LFP half-cell (0.2C, 1C=170mAh / g). It can be seen that the first coulombic efficiency of the battery is 94.5%, which has a high first coulombic efficiency.
[0047] Figure 8 The figure shows the cycling performance of Li4SiO4@rGO in LFP half-cell (0.5C, 1C=170mAh / g). It can be seen that the capacity retention rate of the battery after 100 cycles is 98.3%, which has a high capacity retention rate.
[0048] Fig. 9Shown is the charge and discharge curve of Li4SiO4@rGO in NCM622 half-cell (0.2C, 1C=174.5mAh / g). It can be seen that the first coulombic efficiency of the battery is 85%, which has a high first coulombic efficiency.
[0049] Fig.10 The figure shows the cycling performance of Li4SiO4@rGO in NCM622 half-cell (1C, 1C=174.5 mAh / g). It can be seen that the capacity retention rate of the battery after 100 cycles is 84%, which has a high capacity retention rate.
[0050] The present invention proposes a technical solution using Li4SiO4@rGO composite spheres (i.e., Li4SiO4@rGO composite materials) as a positive electrode lithium supplement additive, aiming to effectively solve the problem of active lithium consumption caused by the formation of solid electrolyte interface (SEI) film. The composite material combines the advantages of Li4SiO4 and rGO by coating lithium tetrasilicon oxide (Li4SiO4) on reduced graphene oxide (rGO), providing controllable electrochemical activity. Experiments show that the Li4SiO4@rGO composite material has a high specific capacity of about 820 mAh / g, which can effectively replenish the lithium ions lost during the operation of the battery. In addition, the design of Li4SiO4@rGO is compatible with the current mainstream battery manufacturing process, ensuring that it has good environmental stability during the manufacturing process and can be easily integrated into the slurry mixing.
[0051] The decomposition products of Li4SiO4@rGO are chemically stable solid components (such as SiO2). These products can maintain good chemical stability, and the generated gases can be safely released during the molding stage, avoiding negative impacts on battery performance. Experimental results show that the Li4SiO4@rGO composite material has a tightly embedded structure, which enables Li4SiO4 to effectively decompose within the normal electrode operating voltage range and release more than 90% of the lithium supplement capacity, significantly improving the energy density and service life of the battery.
[0052] In the electrochemical performance test, the Li4SiO4@rGO composite material performed very well in both LFP and NCM622 half-cells. Specifically, Figure 7 and Figure 8 It shows that the first coulombic efficiency of Li4SiO4@rGO in LFP half-cell reaches 94.5%, and the capacity retention rate after 100 charge and discharge cycles is as high as 98.3%, showing extremely high stability and good cycle performance; Fig. 9 and Fig.10It shows that in the NCM622 half-cell, the first coulombic efficiency of Li4SiO4@rGO is 85%, and the capacity retention rate after 100 cycles is 84%, which also shows excellent electrochemical performance.
[0053] In summary, the Li4SiO4@rGO composite material of the present invention not only has excellent electrochemical properties, such as high specific capacity, good first coulombic efficiency and excellent cycle stability, but also can effectively solve the problem of active lithium consumption in traditional lithium batteries through its unique design, and has significant application prospects and market value.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the scope of the present invention should be included in the protection scope of the present invention.
Claims
1. A Li4SiO4@rGO composite material, characterized in that: It comprises lithium orthosilicate and reduced graphene oxide, wherein the added mass of the reduced graphene oxide is 1%-30% of the total mass of the lithium orthosilicate and the reduced graphene oxide, and the surface of the lithium orthosilicate particles in the Li4SiO4@rGO composite material is coated with a reduced graphene oxide layer; The particle size of the lithium orthosilicate particles is 1-3 μm, and the reduced graphene oxide layer is 20-500 nm.
2. The Li4SiO4@rGO composite material according to claim 1, characterized in that: The added mass of the reduced graphene oxide is 5%-25% of the total mass of lithium orthosilicate and reduced graphene oxide.
3. The method for preparing the Li4SiO4@rGO composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) mixing lithium nitrate and silicon dioxide, and calcining to obtain lithium orthosilicate powder; (2) Dispersing lithium orthosilicate powder evenly in a solvent, adding reduced graphene oxide, and ball milling to obtain a Li4SiO4 / rGO solution; (3) The Li4SiO4 / rGO solution is pumped into a spray dryer to obtain Li4SiO4@rGO composite spheres, thereby obtaining a Li4SiO4@rGO composite material.
4. The method for preparing the Li4SiO4@rGO composite material according to claim 3, characterized in that: In step (1), the molar ratio of lithium nitrate to silicon dioxide is 3-5:
1.
5. The method for preparing the Li4SiO4@rGO composite material according to claim 3, characterized in that: In step (1), the calcination temperature is 650-800°C and the calcination time is 3-5h.
6. The method for preparing the Li4SiO4@rGO composite material according to claim 3, characterized in that: In step (2), the solvent is one or more of water, methanol, ethanol, and N-methylpyrrolidone.
7. The method for preparing the Li4SiO4@rGO composite material according to claim 3, characterized in that: In step (2), the rotation speed of the ball mill is 200-400 rad / min, and the ball milling time is 4-6 h.
8. The method for preparing the Li4SiO4@rGO composite material according to claim 3, characterized in that: In step (3), the inlet temperature of the spray drying is 130-180°C, and the pumping rate of the spray drying is 1-30 ml / min.
9. Use of the Li4SiO4@rGO composite material according to any one of claims 1 to 2 or the Li4SiO4@rGO composite material prepared by the preparation method according to any one of claims 3 to 8 in lithium-ion batteries.
Citation Information
Patent Citations
Lithium supplementing composite diaphragm and preparation method thereof
CN112271405A
Lithium orthosilicate composite material and preparation method and application thereof
CN112467122A
Lithium ion battery and anode lithium supplementing method thereof
CN114583296A
Lithium supplement agent suitable for high-voltage positive electrode as well as preparation method and application of lithium supplement agent
CN115863797A
Composite lithium supplementing material and preparation method thereof, lithium supplementing coating and preparation method thereof, and lithium battery
CN116799210A